Cybersecurity education for awareness and compliance - Vasileiou, Ismini 1980-; Furnell, Steven 1970- (IGI Global, 2019)
"This book provides businesses and organizations with a clear understanding of what security education is, the elements required to achieve it, and how to instill good security behavior and compliance. The chapters draw upon both theoretical principles and practical experience in order to consider what must be done and how to achieve it"--
Description based on title screen (IGI Global, viewed 04/06/2019)
Keywords: Business enterprises / Computer networks / Security measures; Information technology / Security measures; Employees / Training of; Employee rules